Gambaran Darah Kambing yang Bunting Tunggal dan Kembar (Hematological Parameters of does Bearing different Fetal Numbers) - H Maheswari; B Isdoni; Aryani Sismin S; D R Ekastuti; N Kusumorini (Media Peternakan, 2001)
Gambaran Darah Kambing yang Bunting Tunggal dan Kembar (Hematological Parameters of does Bearing different Fetal Numbers)